The effects of geomorphic controls on sediment yield in the Andean Rivers of Colombia - Juan D. Restrepo; Sergio A. López; Juan C. Restrepo (Latin American Journal of Sedimentology and Basin Analysis)
This paper examines sediment yield rates and its response to control variables in the principal rivers of Colombian draining into the Caribbean and Pacific coasts. Based on a multi-year dataset of sediment load from six rivers, including Mira, Patía, and San Juan on the Pacific margin, and Magdalena, Atrato, and Sinú, on the Caribbean basin, various morphometric, hydrologic, and climatic variables were estimated in order to understand and predict the variation in sediment yield. A multiple regression model, including two control variables, runoff and relief ratio (the ratio of the maximum height of the drainage basin and the basin length), explains 83% of the variance in sediment yield. This model is efficient (ME = 0.93) and is a valuable tool for predicting total sediment yield from Colombian rivers. These two selected estimators refer to the relative importance of the fluvial transport component in the sediment routing system. Thus, regional-scale variance of sediment yield in the Andean basins of Colombia seems to be explained by the combined influence of tectonics (relief) and surface runoff available for weathering and transport processes. In general, high sediment yielded rivers are high runoff systems with narrow alluvial plains (i.e. Pacific rivers), while low sediment yielded rivers like the Caribbean systems, contain large sections with not significant gradient in their longitudinal profiles. These sections coincide with large floodplains, which all provide sediment storage capacity within the catchments. When considering the three gauged Pacific rivers at their furthest downstream stations, the combined annual sediment load from these rivers into the Pacific Ocean is ~40 Mt yr-1. In contrast, the Magdalena, Atrato and Sinu rivers deliver ~173 Mt yr-1 into the Caribbean. Overall, Andean rivers of Colombia exhibit the highest sediment yields of all medium-large sized rivers of South America due to the interplay of (1) high rates of runoff (1,750-7,300 mm yr-1), (2) steep relief within catchments, (3) low values of discharge variability (Qmax-Qmin), and (4) episodic sediment delivery due to either geologic events or climatic anomalies.